The abandoned empress. 6 - 인아 (Yen Press, 2023)
Princesses arrive from neighboring kingdoms for the festival, each one intent upon replacing Aristia next to Ruveliss, making the dancefloor a battlefield as treacherous as any war zone. As they use one dirty trick after another to humiliate her in attempts to turn the prince against her, she receives assistance from unexpected allies.